1996
DOI: 10.1042/bj3160943
|View full text |Cite
|
Sign up to set email alerts
|

P2u purinoceptor regulation of mucin secretion in SPOC1 cells, a goblet cell line from the airways

Abstract: The SPOC1 cell, a novel goblet cell line derived from rat trachea, was tested for its ability to exhibit regulated mucin secretion in response to purinergic (P2) agonists. High-molecular mass glycoconjugates (HMMGs) purified by CsCl-density-gradient centrifugation had a buoyant density of 1.45 g/ml. The purified HMMG material exhibited a single major band with an apparent molecular mass of greater than 1000 kDa in SDS/ polyacrylamide gels stained with silver or blotted and stained with soya-bean agglutinin. [3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
65
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 32 publications
2
65
0
Order By: Relevance
“…MUC5AC and MUC5B are the major gel-forming mucins in both bovine cervical mucus and human respiratory mucus (43)(44)(45). To produce large volumes of purified MUC5AC/5B mucins, 50 ml of fresh bovine cervical mucus was solubilized in 6 M guanidinium chloride, and mucins were purified by double isopycnic density gradient centrifugation (46). Fractions were collected, weighed for density, and assessed for DNA (A 260 ), protein (A 270 ), and sialic acid.…”
Section: Methodsmentioning
confidence: 99%
“…MUC5AC and MUC5B are the major gel-forming mucins in both bovine cervical mucus and human respiratory mucus (43)(44)(45). To produce large volumes of purified MUC5AC/5B mucins, 50 ml of fresh bovine cervical mucus was solubilized in 6 M guanidinium chloride, and mucins were purified by double isopycnic density gradient centrifugation (46). Fractions were collected, weighed for density, and assessed for DNA (A 260 ), protein (A 270 ), and sialic acid.…”
Section: Methodsmentioning
confidence: 99%
“…1 (3)(4)(5)(6) or cGMP-dependent protein kinase (PKG) (7) in the secretory process. However, coordinated interactions or "cross-talk" between these two protein kinases in regulation of mucin secretion have not been demonstrated, nor have signaling events downstream of protein kinase activation that ultimately lead to the exocytotic release of mucin granules been elucidated.…”
mentioning
confidence: 99%
“…Standard curves were generated from purified SPOC1 mucins applied to each plate, and the results were expressed as nanograms mucin released per culture. Importantly, in Western blots analyses of SPOC1 cell extracts, soybean agglutinin stains only high-molecular-weight glycoconjugates (3).…”
Section: Methodsmentioning
confidence: 99%
“…Two such mediators, the nucleotides ATP and UTP, appear to be major agonists in goblet cell mucin secretion acting via P2Y 2 purinoceptors (P2Y 2 -Rs) (15,17,31,62). P2Y 2 -R activation by agonist elicits a coupling with PLC via G q , production of the primary intracellular messengers diacylglycerol (DAG) and inositol-1,4,5-trisphosphate (IP 3 ) from phosphatidylinositol-4,5-bisphosphate (PIP 2 ), followed by activation of protein kinase C (PKC) and mobilization of Ca 2ϩ (62). Pharmacological studies in goblet cells have shown that mucin secretion can be stimulated via intracellular messenger pathways by the DAG mimic phorbol-1,2-myristate-13-acetate (PMA) (15,17,30,31), by IP 3 (52), and by the Ca 2ϩ -mobilizing agents ionomycin and thapsigargin (15,30,51).…”
mentioning
confidence: 99%